Demonstration of neutrinoless double beta decay searches in gaseous xenon with NEXT - Fernandes, L. M. P. (2023)
The NEXT experiment aims at the sensitive search of the neutrinoless double beta decay in $^{136}$Xe, using high-pressure gas electroluminescent time projection chambers. The NEXT-White detector is the first radiopure demonstrator of this technology, operated in the Laboratorio Subterr\'aneo de Canfranc. Achieving an energy resolution of 1% FWHM at 2.6 MeV and further background rejection by means of the topology of the reconstructed tracks, NEXT-White has been exploited beyond its original goals in order to perform a neutrinoless double beta decay search. The analysis considers the combination of 271.6 days of $^{136}$Xe-enriched data and 208.9 days of $^{136}$Xe-depleted data. A detailed background modeling and measurement has been developed, ensuring the time stability of the radiogenic and cosmogenic contributions across both data samples. Limits to the neutrinoless mode are obtained in two alternative analyses: a background-model-dependent approach and a novel direct background-subtraction technique, offering results with small dependence on the background model assumptions. With a fiducial mass of only 3.50$±$0.01 kg of $^{136}$Xe-enriched xenon, 90% C.L. lower limits to the neutrinoless double beta decay are found in the T$_{1/2}^{0ν}>5.5×10^{23}-1.3×10^{24}$ yr range, depending on the method. The presented techniques stand as a proof-of-concept for the searches to be implemented with larger NEXT detectors.